1998
DOI: 10.1135/cccc19980741
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH on Phosphate Intercalation in Zinc-Aluminum Layered Double Hydroxide

Abstract: The exchange of chloride ion by phosphate ions in [Zn-Al-Cl] layered double hydroxide was investigated using X-ray diffraction and infrared spectroscopy. The effects of the pH of the solution containing the phosphate ions on the ion exchange was studied. The best sample in terms of crystallinity, was obtained at pH 8. This sample was further characterized by scanning electron microscopy and microanalysis.Layered double hydroxides (LDH)s, also called anionic clays or hydrotalcite-like compounds 1 , are layered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…The spectroscopy of this unit would be very different from the free phosphate anions. Badreddine et al 37,39 in a series of papers reported the infrared spectra as well as the PXRD spectra of Zn/Al LDH's Raman spectra of free phosphate oxyanions as in aqueous solutions show the symmetric stretching mode 1 at 938 cm 1 , the antisymmetric stretching mode 3 at 1017 cm 1 , the symmetric bending mode 2 at 420 cm 1 The Raman spectra of the hydrotalcites formed at different pH are shown in Fig. 4.…”
Section: Raman Spectroscopymentioning
confidence: 97%
See 1 more Smart Citation
“…The spectroscopy of this unit would be very different from the free phosphate anions. Badreddine et al 37,39 in a series of papers reported the infrared spectra as well as the PXRD spectra of Zn/Al LDH's Raman spectra of free phosphate oxyanions as in aqueous solutions show the symmetric stretching mode 1 at 938 cm 1 , the antisymmetric stretching mode 3 at 1017 cm 1 , the symmetric bending mode 2 at 420 cm 1 The Raman spectra of the hydrotalcites formed at different pH are shown in Fig. 4.…”
Section: Raman Spectroscopymentioning
confidence: 97%
“…While there have been some infrared studies of phosphate interlayered hydrotalcites, there have been no Raman spectroscopic studies. 37 -40 Adsorption of HPO 4 2 ions on a nitrate hydrotalcite resulted in characteristic infrared bands 41 between 37,39,42 between 1064 and 1067 cm 1 as well as 988 cm 1 . Thus, a comparison of the two sets of data shows that the anion is held between the hydrotalcite layers electrostatically and is not bonded to the hydrotalcite surface.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…There is an equal likelihood for the formation of unitary (comprising a single metal ion) salts of the incoming anion. Thus phosphates tend to combine with the metal ions to yield metal phosphates, rather than phosphate intercalated LDHs [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…HT consists of positively charged brucite-like octahedral layers formed by partial substitution of Al for Mg and interlayer carbonate ion, and is represented by the chemical formula Mg 6 Al 2 (OH) 16 CO 3 ·4H 2 O. HTs are commonly synthesized in industrial fields for use in products such as resin additives and antacids for the stomach [3][4][5] , and LDHs are often studied for application as scaffolds for immobilizing functional organic species [6][7][8] . The sorption of phosphate ions with LDHs from aqueous solution is an attractive method to secure phosphate resources and has been studied by many researchers [9][10][11][12][13][14][15][16][17][18] . In general, these anion-exchange reactions are conducted by using LDHs with chlorate or nitrate ions in the interlayer, because it is difficult to exchange carbonate ions incorporated on the LDH structure with external anions because of the strong affinity of carbonate anions toward the brucite-like layer 19,20 .…”
Section: Introductionmentioning
confidence: 99%